The use of mixed algae species as biocathode in membrane-less microbial fuel cell - Banu Taşkan (Firat University Journal of Experimental and Computational Engineering, 2022)
Membrane-less microbial fuel cell (MLMFC) is one of the most promising technologies for energy generation from organic wastes. The use of biocathode in the MLMFC system reduces the operation cost and provides many benefits. In an algal MLMFC system, the photosynthetic microorganism facilitates the oxygen reduction in the cathode chamber and improves overall cell performance. However, the assessment of the long-term stability of biocathode is a primary concern. In the current study, the electricity generation performance of algal MLMFC using mixed-algae as a biocathode was investigated. The results showed that the electricity generation of algal MLMFC increased during the light cycle because of the photosynthesis of algal cells in the cathode. During the light cycle, the maximum power density and lowest cathode charge transfer resistance of algal MLMFC were 215.71 mW/m2 and 29.73 Ω, respectively. The electrochemical analysis demonstrated that the anode biofilm of algal MLMFC has high bioelectrogenic activity. This study plays a crucial role in determining the applicability of this technology.